Trimethylamine N-oxide and incident atherosclerotic events in high-risk individuals with diabetes: an ACCORD trial post hoc analysis. Issue 1 (15th November 2019) - Cardona, Andrea; O'Brien, Aaron; Bernier, Matthew C; Somogyi, Arpad; Wysocki, Vicki H; Smart, Suzanne; He, Xin; Ambrosio, Giuseppe; Hsueh, Willa Ann; Raman, Subha V
Abstract : Introduction: Type 2 diabetes mellitus (T2D) confers high atherosclerotic cardiovascular disease (ASCVD) risk. The metabolite trimethylamine N-oxide (TMAO) derived via gut flora has been linked to excess ASCVD. Research design and methods: We analyzed data, biospecimens, and major adverse cardiovascular events (MACEs) from the prospective multicenter randomized Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial to assess its value in 330 high-risk individuals with T2D without evident atherosclerotic disease at enrollment. Results: Incident cardiovascular events occurred in 165 cases; 165 controls matched by age, sex, and treatment arm experienced no incident events during follow-up. Cases and controls (mean age 64.5 years) had similar mean glycated hemoglobin (HbA1c) (8.2%) and mean 10-year ASCVD risk (23.5%); groups also had similar use of statins and antihypertensive medications at baseline and follow-up. Baseline plasma TMAO levels did not differ between groups after adjusting for ASCVD risk score, HbA1c, and estimated glomerular filtration rate, nor did TMAO distinguish patients suffering incident MACE from those who remained event-free. Conclusions: TMAO's prognostic value for incident ASCVD events may be blunted when applied to individuals with T2D with poor glycemic control and high baseline ASCVD risk. These results behoove further translational investigations of unique mechanisms of ASCVD risk in T2D.